Pengaruh kombinasi gula aren dan samu dalam proses fermentasi daging ikan Mas (Cyprinus carpio) - Restu Restu (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
“Wadi” is a processed product of salted fish and added with “samu”, then stored for at least seven days for the fermentation process. The purpose of this research is to know the influence of combination of samu with palm sugar as a medium of growth of lactic acid bacteria in the process of fermentation of carp (Cyprinus carpio), in order to accelerate the fermentation process. The results showed that the combination of samu and palm sugar could accelerate the process of fermentation of carp into three days. The best treatment was combination of 4% samu and 2% palm sugar. Water content test resulted 61.11%; texture 0.143 - 0.152 mm/gr/s; and the mean value of the preferred test level on appearance, odor and taste was 7.6 with criteria favored by panelists. Key words : fermentation, carp (Cyprinus carpio), samu, palm sugar